New records of neonate and juvenile sharks (Heptranchias perlo, Squatina aculeata, Etmopterus spinax) from the North-eastern Mediterranean Sea - Basusta, Nuri (Springer Heidelberg, 2016)
Three species of neonate and juvenile sharks (Heptranchias perlo, Squatina aculeata, Etmopterus spinax) were captured as by-catch from a commercial trawl fishing from depths between 360 and 430 m in the North-eastern Mediterranean Sea. Two neonates of H. perlo, five neonates of E. spinax and one juvenile of S. aculeata were for the first time identified in the above region.
Keywords: Heptranchias perlo; Squatina aculeata; Etmopterus spinax; Sharpnose sevengill shark; Sawback angelshark; Velvet belly; North-eastern Mediterranean